2016
DOI: 10.1027/1614-2241/a000111
|View full text |Cite
|
Sign up to set email alerts
|

Pooling ANOVA Results From Multiply Imputed Datasets

Abstract: Abstract. The analysis of variance (ANOVA) is frequently used to examine whether a number of groups differ on a variable of interest. The global hypothesis test of the ANOVA can be reformulated as a regression model in which all group differences are simultaneously tested against zero. Multiple imputation offers reliable and effective treatment of missing data; however, recommendations differ with regard to what procedures are suitable for pooling ANOVA results from multiply imputed datasets. In this article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…Imputation has advantages over alternative methods to address missing data in diallel experiments in that it is relatively simple to implement, makes use of all available data for a given trait, and replaces missing data with plausible estimates to avoid reductions in sample size. However, there are several caveats and compromises regarding multiple imputation, namely, that there are inadequate or vague diagnostics and, although simple in principle, methods to pool multi-factor ANOVA results are often vague, or are not widely accessible ( van Ginkel and Kroonenberg 2014 ; Grund et al 2016 ). In this study, we demonstrate the application of existing, relatively straightforward, methods to pool results for diallel analysis across multiple environments.…”
Section: Discussionmentioning
confidence: 99%
“…Imputation has advantages over alternative methods to address missing data in diallel experiments in that it is relatively simple to implement, makes use of all available data for a given trait, and replaces missing data with plausible estimates to avoid reductions in sample size. However, there are several caveats and compromises regarding multiple imputation, namely, that there are inadequate or vague diagnostics and, although simple in principle, methods to pool multi-factor ANOVA results are often vague, or are not widely accessible ( van Ginkel and Kroonenberg 2014 ; Grund et al 2016 ). In this study, we demonstrate the application of existing, relatively straightforward, methods to pool results for diallel analysis across multiple environments.…”
Section: Discussionmentioning
confidence: 99%
“…Barnard and Rubin (1999) and Reiter (2007) developed improved error degrees of freedom for these combination rules. Simulation studies (Barnard & Rubin, 1999;Grund, L€ udtke, & Robitzsch, 2016;Liu & Enders, 2017;Reiter, 2007;Schafer, 1997) have shown that these combination rules generally give type-I error rates close to the theoretical type-I error rates.…”
Section: Introductionmentioning
confidence: 84%
“…For testing several parameters for significance simultaneously, several solutions are available Meng & Rubin, 1992;Rubin, 1987). Of these solutions, the most promising one Rubin, 1987) according to several simulation studies (Grund et al, 2016;Liu & Enders, 2017;Reiter, 2007) is a set of formulas that are multivariate extensions of Equations (3)-(8).…”
Section: Multiparameter Estimatesmentioning
confidence: 99%
“…In addition to Rubin's rules (1987), the package implements the procedures commonly referred to as D 1 Reiter, 2007), D 2 (Li, Meng, Raghunathan, & Rubin, 1991), and D 3 (Meng & Rubin, 1992), which can be used for testing a variety of statistical hypotheses that potentially involve multiple parameters simultaneously (e.g., model comparisons Li, Meng, et al (1991) and Meng and Rubin (1992), or on variations thereof (Licht, 2010), but clear recommendations have not yet been made in the literature (see also Consentino & Claeskens, 2010;Grund, Lüdtke, & Robitzsch, 2016b).…”
Section: Discussionmentioning
confidence: 99%